Innovative and Marketing Features of Agri-Food Supply Chain Development - YASNOLOB, Ilona; DEMIANENKO, Nataliia; GORB, Oleg; TIUTIUNNYK, Yurii; TIUTIUNNYK, Svitlana; SHULGA, Lyudmyla; DUGAR, Tetiana; MAIBORODA, Olena; PYSARENKO, Svitlana; POMAZ, Yuliia (Journal of Environmental Management and Tourism; Vol 14 No 7 (2023): JEMT, Volume XIV, Issue 7(71), Winter 2023DO - 10.14505/jemt.v14.7(71).03, 2023)
The article emphasises that geopolitical instability (russian aggression in Ukraine, sanctions, tensions between the US and China, inflation, recession) has a negative impact on agri-food chains. In particular, the war in Ukraine is affecting Africa by increasing food prices, destabilising the situation and creating the threat of famine. The article examines the export challenges faced by Ukraine during the war. Smart solutions provided in Ukraine and around the world in order to develop export opportunities are analysed. The specifics of investing in nearshoring production are investigated. The market of “digital logistics” as a set of services and tools for transportation is analysed.  The research studied digital platforms that can effectively manage cross-border transport in a single system and optimise the many business processes involved. Services that help to track real-time information on cargo, their location and transport conditions are analysed. They allow customers to reduce downtime costs, assess the efficiency of carriers, monitor cargo condition and quality.  This article focuses on the warehouse automation industry. In particular, it notes that robotic devices are already capable of sorting parcels, transporting them within warehouses and moving them from one shelf to another. Particular attention is paid to the further transition to safer raw materials. The operators proposed to use green energy sources and support suppliers focused on renewable energy. The main trends in 2023-2024 are expected to be the development of technology, flexibility, further transition to “green” solutions and other ways of developing the logistics market both in Ukraine and globally. It is determined that Ukraine will be rebuild according to the principle of Build Back Better, in particular, it will build everything according to new rules and to the extent required, based on new realities.